STUDI INTERAKSI SEGMEN TRIMER KITOSAN DENGAN ASAM ASKORBAT SECARA KOMPUTASI AB INITIO DAN EKSPERIMEN - Hasanah, Niswatun (Chem Info Journal, 2013)
STUDY of INTERACTION between CHITOSAN TRIMER SEGMENT and ASCORBIC ACID by QUANTUM AB INITIO and EXPERIMENT METHODS. The research has been done between chitosan trimer segments and ascorbic acid used quantum ab initio on theory and basis set RHF/6-31G(d,p) and experiment methods. The quantum ab initio method could be used to get the geometry structure of molecule that more stable and characteristics of intermolecular interaction in the gas phase as simulation of experiment method which too expensive. The aim of research is to determine interaction energy between chitosan trimer segment and ascorbic acid and determine encapsulation efficiency of chitosan on ascorbic acid concentration is 500 ppm. The result show that the interaction can occur between chitosan trimer segment and ascorbic acid with each energy of them were the first and the second configuration respectively -38.1538 kJ.mol-1 and -29.7388 kJ.mol-1. The first configuration position was preferred to others because its energy was greater. Its conclusion was interaction between chitosan trimer segment and ascorbic acid was medium hydrogen bond then the experiment result also prove the interaction between chitosan trimer segment and ascorbic acid shown by free ascorbic acid, filtrate of centrifugation result with encapsulation efficiency of chitosan 64.38 % for ascorbic acid 500 ppm.